Three exonic variants in the PHEX gene cause aberrant splicing in a minigene assay - Pan, Fengjiao; Zhang, Ruixiao; Liu, Xuyan; Shi, Xiaomeng; Xin, Qing; Qiao, Dan; Li, Changying; Zhang, Yan; Chen, Mengke; Guo, Wencong; Luan, Shufang; Shao, Leping (Frontiers in Genetics, 2024)
ABSTRACT Background: X-linked hypophosphatemia (XLH, OMIM 307800) is a rare phosphorus metabolism disorder caused by PHEX gene variants. Many variants simply classified as missense or nonsense variants were only analyzed at the DNA level. However, growing evidence indicated that some of these variants may alter pre-mRNA splicing to cause diseases. Therefore, this study aimed to use bioinformatics tools and a minigene assay to ascertain the effects of PHEX variations on pre-mRNA splicing. Methods: We analyzed 174 variants in the PHEX gene described as missense or nonsense variants. Finally, we selected eight candidate variants by bioinformatics tools to evaluate their effects on pre-mRNA splicing using a minigene assay system. The complementary DNA (cDNA) sequence for PHEX (RefSeq NM_000444.6) serves as the basis for DNA variant numbering. Results: Of the eight candidate variants, three were found to cause abnormal splicing. Variant c.617T>G p.(Leu206Trp) and c.621T>A p.(Tyr207*) in exon 5 altered the splicing of pre-mRNA owing to the activation of a cryptic splice site in exon 5, which produced an aberrant transcript lacking a part of exon 5. Whereas, variant c.1700G>C p.(Arg567Pro) in exon 16 lead to the activation of a cryptic splice site in intron 16, resulting in a partial inclusion of intron16. Conclusion: Our study employed a minigene system, which has a great degree of flexibility to assess abnormal splicing patterns under the circumstances of patient mRNA samples are not available, to explore the impact of the exonic variants on pre-mRNA splicing. Based on the aforementioned experimental findings, we demonstrated the importance of analyzing exonic variants at the mRNA level.